2021
DOI: 10.3390/jcm10153383
|View full text |Cite
|
Sign up to set email alerts
|

Submassive Pulmonary Embolism: Current Perspectives and Future Directions

Abstract: Submassive pulmonary embolism (PE) lies on a spectrum of disease severity between standard and high-risk disease. By definition, patients with submassive PE have a worse outcome than the majority of those with standard-risk PE, who are hemodynamically stable and lack imaging or laboratory features of cardiac dysfunction. Systemic thrombolytic therapy has been proven to reduce mortality in patients with high-risk disease; however, its use in submassive PE has not demonstrated a clear benefit, with haemodynamic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 97 publications
0
9
0
Order By: Relevance
“…Growing data suggest that specific high-risk patients with massive or submassive PE and/or clot in transit may have both survival and symptomatic benefit from advanced therapies in comparison to anticoagulation alone [ 1 , 3 7 , 9 10 ]. Long-term data for catheter-related therapies are lacking and mostly based on smaller case series [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Growing data suggest that specific high-risk patients with massive or submassive PE and/or clot in transit may have both survival and symptomatic benefit from advanced therapies in comparison to anticoagulation alone [ 1 , 3 7 , 9 10 ]. Long-term data for catheter-related therapies are lacking and mostly based on smaller case series [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this approach, an aspiration cannula is inserted into one of the major veins and connected to a veno-venous bypass circuit which then captures the aspirated debris. Although there have been case series that focus on the reduction in thrombus burden and hospital survival, data are lacking on the impact of these devices long-term on survival and patient outcomes [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The standard dosage of alteplase for PE is 100 mg over 2 h.[ 6 ] A recent report compared the 100 mg/2 h and 50 mg/2 h regimens which found that the reduced dosage exhibits similar efficacy and perhaps better safety profile. [ 7 ] Another case series used rtPA for sub-massive PE using 10 mg IV bolus over 1 min and continued with 40 mg IV over 2 h.[ 8 ]…”
Section: Discussionmentioning
confidence: 99%
“…Because patients with submassive PEs do not exhibit abnormal hemodynamics, they may be initially indistinguishable from low-risk PEs before the objective testing required to demonstrate cardiac dysfunction. Up to 10% of patients with submassive PEs may decompensate and progress toward massive PE 31 …”
Section: Risk Stratificationmentioning
confidence: 99%
“…Up to 10% of patients with submassive PEs may decompensate and progress toward massive PE. 31 PEs that do not cause heart strain or hemodynamic compromise are considered low-risk. 4(p1) Low-risk PEs generally pose a low mortality risk, with evidence showing little to no benefit from hospitalization after treatment is initiated.…”
Section: Risk Stratificationmentioning
confidence: 99%